Владимир Алексеевич Водяницкий — гидробиолог и организатор науки - (:unkn) unknown (Киев : Наук. думка, 1974)
Дан обзор трех основных направлений работ члена-корреспондента АН УССР В. А. Водяницкого: исследование ихтиопланктона Черного моря; изучение его биологической продуктивности и теоретическая разработка проблемы биологической продуктивности морей; теоретическое обоснование процесса водообмена в Черном море. Кратко освещается научно-организационная деятельность В. А. Водяницкого.
Vladimir Aleichem Vodyanitsky — a hydrobiologist and organizer of science
A review is presented of trends in researches performed by V. A. Vodyanitsky, Corresponding Member of the Ukrainian Academy of Sciences: studies of the Black Sea ichthyoplankton and development of the hypothesis on formation of the Black Sea ichthyotauna; studies of biological productivity in the Black Sea and a theoretical development of biological productivity in water bodies; development of a diagram for the Black Sea water exchange. Organization activity of V. A. Vodyanitsky as director of the Sevastopol Biological Station and Institute of Biology of Southern Seas of the Ukrainian Academy of Sciences is also dealt with in short.